Diagnostic Utility of EMA, Vimentin and CD117 Immunohistochemical Markers in Subtyping Renal Cell Carcinoma in a Nigerian Tertiary Hospital: A 10-year Retrospective Study. (2023)
BACKGROUND: Renal cell carcinoma is the most lethal urological cancer and contributes significantly to morbidity and mortality due to cancers of the urogenital tract. In routine diagnostic surgical pathology practice of renal tumours, immunohistochemistry is a helpful ancillary technique after routine H & E. The role of renal immunohistochemistry is explored in this study. MATERIALS AND METHODS: The paraffin-embedded tissue blocks of all the confirmed cases of renal cell carcinoma seen at the University College Hospital (UCH), Ibadan, during the 10-year study period of 2007 to 2016 were retrieved, sectioned and immunohistochemistry done using monoclonal antibodies for EMA, Vimentin and CD117 following standard protocols. Frequency statistics and chi-square were applied to data to determine proportions and associations using the Statistical Package for the Social Sciences (SPSS) version 23. RESULTS: A total of 48 cases of renal cell carcinoma were seen within the study period that met the inclusion criteria for the study. The age range of the patients was between 3 to 76 years with an average age of 44.17 years. The male-to-female ratio was 1:1.3. Fuhrman Grade 2 nuclei were predominant (43.75%) while Fuhrman Grade 4 nuclei had the lowest frequency (6.25%). EMAstaining patterns for the different histological patterns of RCC showed no statistically significant difference while Vimentin and CD117 staining patterns showed a statistically significant difference. There was no statistically significant difference observed between the staining patterns of all three markers and the nuclear grades of the cases of RCC. CONCLUSION: This study demonstrated the usefulness of Vimentin and CD117 in differentiating chromophobe variant of renal cell carcinoma from other subtypes while EMA showed variable expression across the various subtypes. WAJM 2023; 40(10); 1035 -1040.